APLIKASI BOOKING FITTING PAKAIAN PADA TOKO REKHAS TEXTILE BERBASIS WEB - Angeline Alviona Meilyta; Tony Tony; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
The Apparel Booking Fitting Application on the Web-Based Rekhas Textile Store is an application designed to make easier for customers to book fittings because through this application, customers can see products and determine their own fitting schedule without having to go directly to the store and also help the store in recording and processing booking fitting data efficiently and effectively. The process of booking fittings at the Rekhas Textile Store is still using the manual method, namely the customer comes directly to the store to make a booking fitting by selecting the desired product and the management of the booking fitting data at the Rekhas Textile Store is done by recording via excel files, scheduling booking fittings is still done by the employees. This application uses the Waterfall System Development Life Cycle (SDLC) development methodology. The database used in this application is MySQL. The programming languages used are HTML and PHP with the CodeIgniter framework.